Delayed diagnosis and management of necrotizing fasciitis of the left lower leg: A case report. Issue 43 (28th October 2022) - Zhang, Li-Xia; Liang, Zhao-Jun; Zhao, Bao-Yin; Shi, Xue-Wen; Zhang, Tao; Liu, Hua; Yu, Xiao-Hui
Abstract : Introduction: Necrotizing fasciitis (NF) is a rare, severe soft tissue infection, characterized by rapid and extensive necrosis of the skin, subcutaneous tissue, and superficial and deep fascia. It is frequently misdiagnosed as other infectious diseases, leading to inappropriate treatment and potentially serious consequences. It may be complicated by septic shock and multiple organ failure with a fatal outcome. Patient concerns: A 73-year-old woman presented with continuous itching, skin lesions, pain, and swelling of the outer side of her left leg. The patient was diagnosed with septic shock and multiorgan failure caused by left leg NF. Diagnosis: Septic shock and multiorgan failure caused by left leg NF. Interventions: Two surgeries were performed on the patient's leg, which effectively treated her septic shock and multiple organ dysfunction. Outcomes: The patient was followed up three times after her discharge. She had a good recovery, was generally well with no significant sequelae, and returned to her regular life. Conclusion: NF is an acute severe illness with high mortality. It is easily misdiagnosed, leading to delayed or erroneous treatment and serious (or potentially fatal) outcomes. Rapid and accurate diagnosis of NF is essential for patient recovery. In difficult cases, multidisciplinary consultations may be helpful. The management of NF includes early and thorough surgical debridement, antibiotics, and symptomatic treatment.